Überlegungen zu einem neuen zweisprachigen phraseologischen Wörterbuch Deutsch–Rumänisch - Sava, Doris (Lexikos, 2017)
Considerations on a New Bilingual German–Romanian Phraseological Dictionary.The conventional Romanian bilingual phraseography with German contains significant shortcomings regarding both the conceptual orientation of the dictionary and the structure of the dictionary articles. Taking into account the results of specialised bilingual lexicography worldwide and the usefulness of existing dictionaries from a current perspective, it becomes obvious that it is imperative to promote the creation of a modern phraseological dictionary which will be more reliable and user-friendly than the existing works. When the restructuring of the existing phraseological lexica for Romanian-speaking users of the German language is considered, the main concern must be the creation of a reference book which will meet higher requirements regarding the selection of material and the codification practice. Thus, this article points out possible improvements to the Romanian bilingual lexicographical description of phraseological units with German, whereby the presented lexicographical description model offers relevant information for the reception and production of the presented idioms.